History and development of medical ethics- the international norms - Shah, Jay N. (Journal of Patan Academy of Health Sciences, 2019)
Medical ethics encompasses a broad field, including ethics in day to day medical practice, in research and publication. The historical development in the context of international norms of medical ethics is presented here, with brief mention of ‘research and publication ethics’, the latter two being a broad topic in itself.